An€álise da resposta de Paracoccidioides brasiliensis a diferentes tipos de agentes estressores e osmoreguladores e express o heteró‚loga e localizaçãƒ o de β-1.3-glicana sintase - TOMAZETT, Patrícia Kott (2010)
Paracoccidioides brasiliensis is a thermo-dimorphic human pathogenic fungus that lives at 23”C in the mycelium phase (infecting phase) and at 37”C in the yeast phase (parasite phase). In attempt to survive, the cell wall of fungi can change its composition and/or structure in response to environmental stress by compensatory mechanisms. The molecules involved in these mechanisms are possible target for the development of effective antifungal agents. In P. brasiliensis, the main components of the cell wall are glucans and chitin polymers. These polymers make a primary barrier that is responsible for the structural integrity and form of the cell wall. In this work the behavior of P. brasiliensis was evaluated against stress conditions with the aim of study, for the first time, the mechanisms used by this fungus in the maintenance of the cell wall integrity. Our results shown that P. brasiliensis yeast cells are sensitive to cell wall stressors calcofluor white (CFW), congo red (CR), SDS, KCl, NaCl and sorbitol. There was an increase in the PbFKS1 transcripts expression and in the content of cell wall β- 1,3-glicana after treatment with all stressor agents. After treatment with SDS and KCl the PbGFA1 transcripts expression and the cell wall GlcNAc residues also increased. The transcript expression of PbGEL3 was also evaluated being increased after treatment with CFW, NaCl and sorbitol. Thus we showed that these molecules are involved in the maintenance of the cell wall against stress conditions. Apart from these analyses we obtained the active recombinant protein PbFks1pc. Through the anti-PbFks1pc antibody we performed immunocitolocalization assays. These experiments revealed the localization of PbFks1p in regions of apical growth in the mycelium phase and in the cell surface in yeast phase.